Diaphragm and preparation method and application thereof
By modifying the black phosphorus composite material PEDOT-BP coating, the problems of insufficient lithium ion transport and electrolyte wettability of lithium-ion battery separators were solved, high lithium ion conductivity and electrolyte wettability of the separator were achieved, and the safety and cycle performance of the battery were improved.
Patent Information
- Application Number
- CN202510696922.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2025-09-12
AI Technical Summary
Existing lithium-ion battery separators have deficiencies in improving lithium-ion transport and electrolyte wettability, resulting in limited battery safety and performance.
A modified black phosphorus composite material PEDOT-BP is used. Black phosphorus is modified and polymerized with EDOT to form a coating to improve the lithium ion conductivity and electrolyte wettability of the diaphragm. The preparation method includes the preparation of modified black phosphorus, the preparation of diaphragm slurry and the coating process.
The lithium ion conductivity and electrolyte wettability of the separator are improved, thereby enhancing the safety and cycle performance of the battery.
Smart Images

Figure CN120637775A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a diaphragm and a preparation method and application thereof. Background Art
[0002] Lithium-ion secondary batteries, as energy storage devices with high energy density, long service life, and environmental friendliness, are widely used in 3C digital products, aerospace equipment, electric vehicles, and high-tech industries. As energy density continues to increase, the safety of lithium-ion secondary batteries urgently needs to be improved. When lithium-ion batteries are subjected to external stimuli such as impact or needle puncture, or when they are short-circuited or overcharged, they can experience thermal runaway, leading to fire or even explosion. As a key component in lithium-ion batteries, the separator plays a vital role in battery safety. Its primary function in the battery is to prevent direct contact between the positive and negative electrodes, transport ions, and hinder electron transport. To improve the safety of lithium-ion batteries, a common practice is to coat the separator surface with ceramic to further reduce its thermal shrinkage. However, this approach also increases the distance lithium ions can travel, and ceramics have limited wettability with electrolytes. Therefore, a separator with high wettability and high lithium ion conductivity is urgently needed to improve battery performance. Summary of the Invention
[0003] Based on the technical problems existing in the background technology, the present invention proposes a diaphragm and a preparation method and application thereof.
[0004] The present invention provides a method for preparing a diaphragm, comprising the following steps:
[0005] S1, modifying black phosphorus to obtain a modified black phosphorus composite material;
[0006] S2. Mixing the modified black phosphorus composite material, dispersant, water, functional component, thickener, and binder to obtain a diaphragm slurry;
[0007] S3. Apply the diaphragm slurry on the surface of the base film and dry it.
[0008] The diaphragm provided by the present invention can not only improve the wettability of the diaphragm to the electrolyte, but also be used to transmit lithium ions, and has excellent ionic conductivity and capacity retention rate.
[0009] Preferably, in S1, the modification treatment comprises: uniformly mixing black phosphorus, D-(+)-glucose, and a solvent, heating the reaction in a reactor for reaction, washing and drying to obtain hydroxylated black phosphorus; dispersing the hydroxylated black phosphorus in a solvent, adding EDOT and FeCl3 solution, uniformly dispersing, washing, and drying to obtain the product.
[0010] Hydroxylation effectively mitigates the susceptibility of black phosphorus to oxidation due to the presence of lone pairs of electrons. Furthermore, the hydroxyl groups effectively form hydrogen bonds with EDOT, facilitating the in-situ polymerization of EDOT onto the black phosphorus surface to form PEDOT. Adding the modified black phosphorus composite material, PEDOT-BP, to the separator coating effectively improves the separator's lithium-ion conductivity, enhances electrolyte wettability, and ultimately improves battery performance.
[0011] More preferably, the mass ratio of the black phosphorus, D-(+)-glucose and solvent is (1-3):(1-3):(500-900).
[0012] The mass ratio of black phosphorus, D-(+)-glucose, and solvent within a certain range helps to fully hydroxylate the black phosphorus surface, providing sufficient sites for subsequent PEDOT modification on the black phosphorus surface.
[0013] The role of D-(+)-glucose in this invention is to provide hydroxyl groups on the black phosphorus surface. D-(+)-glucose contains a polyhydroxyl structure, which reacts with the lone pair electrons on the black phosphorus surface at high temperatures, chemically bonding the hydroxyl groups to the black phosphorus surface.
[0014] The role of the FeCl3 solution in the present invention is to act as an oxidant to initiate the polymerization reaction of EDOT. The trivalent iron ion has a strong oxidizing property and can oxidize the EDOT monomer into a cationic free radical, thereby initiating a chain polymerization reaction.
[0015] More preferably, the solvent is selected from one or more of N-methylpyrrolidone, acetone, N,N-dimethylformamide, and ethanol.
[0016] More preferably, the heating temperature is 100-200°C.
[0017] Heating temperature within a certain range helps the reaction proceed quickly and efficiently. Too high a temperature may cause degradation of the raw materials, while too low a temperature may reduce the reaction efficiency or prevent it from occurring.
[0018] More preferably, the reaction time is 2 to 10 hours.
[0019] More preferably, the washing detergent is ethanol.
[0020] More preferably, the FeCl3 solution is an ethanol solution of FeCl3, and the concentration of the FeCl3 solution is 0.01 to 0.08 mmol / mL.
[0021] More preferably, the mass ratio of the hydroxylated black phosphorus to the solvent is 1:(500-1000).
[0022] More preferably, the mass ratio of the hydroxylated black phosphorus, EDOT, and FeCl3 solution is (1-3): (1-7): (20-100).
[0023] Preferably, in S1, the method for preparing black phosphorus comprises the following steps: uniformly mixing red phosphorus, tin iodide and tin powder, and calcining to obtain a mixture; stirring the mixture and a dispersant, centrifuging and drying to obtain black phosphorus.
[0024] The black phosphorus prepared by the present invention has a high lithium ion diffusion constant, and the two-dimensional sheet can have a larger specific surface area.
[0025] More preferably, the mass ratio of the red phosphorus, tin iodide and tin powder is (10-30): (2-7): (0.5-2).
[0026] More preferably, the calcination treatment includes first heating to 600-700°C at a rate of 150-200°C / h and keeping warm for 1-2h; then cooling to 450-500°C within 4-5h and keeping warm for 1-2h; then cooling to 200-250°C within 9-10h; and finally cooling to room temperature within 5-6h.
[0027] More preferably, the mass ratio of the mixture to the dispersant is (10-50):(300:600).
[0028] More preferably, the stirring speed is 500 to 20,000 r / min, and the stirring time is 1 to 10 hours.
[0029] More preferably, the dispersant is N-methylpyrrolidone.
[0030] More preferably, the drying comprises maintaining the mixture in a vacuum oven at 40-60° C. for 4-10 hours.
[0031] More preferably, the black phosphorus is nanoscale black phosphorus, and the particle size of the black phosphorus is 200nm to 3000nm.
[0032] Preferably, in S2, the mass ratio of the dispersant, water, modified black phosphorus composite material, thickener, binder and functional component is (0.1-10):100:(0.1-10):(0.5-15):(0.1-10):(10-80).
[0033] The mass ratio of the dispersant, water, modified black phosphorus composite material, thickener, binder, and functional components within a certain range is conducive to forming a stable slurry, which is conducive to uniform coating on the surface of the diaphragm.
[0034] Preferably, in S2, the functional component is selected from one or more of ceramic solid particles and PVDF particles.
[0035] The role of the functional component is to improve the heat resistance of the diaphragm and its adhesion to the electrode.
[0036] More preferably, the ceramic solid particles are selected from one or more of alumina, silica, zirconium oxide, aluminum hydroxide, magnesium hydroxide, boehmite, boron nitride, and silicon oxide.
[0037] Preferably, in S2, the thickener is selected from one or more of sodium carboxymethyl cellulose, carboxymethyl hydroxypropyl cellulose, methyl hydroxyethyl cellulose, and hydroxyethyl cellulose.
[0038] Preferably, in S2, the binder is selected from one or more of water-based polyacrylate, polyurethane acrylate, polyether acrylate, polyurethane, epoxy resin, and polyvinylidene fluoride.
[0039] Preferably, in S2, the dispersant is selected from one or more of polyacrylate sodium salt, polyacrylate potassium salt, polyacrylate ammonium salt, and polycarboxylate sodium salt.
[0040] The role of the thickener is to adjust the rheological properties of the slurry, prevent ceramic particles from settling, and enhance the ability of the coating to hold slurry on vertical surfaces. The role of the binder is to strengthen the adhesion between the ceramic particles and the separator substrate, improving the mechanical strength and heat resistance of the coating. The role of the dispersant is to promote the uniform dispersion of ceramic particles (such as alumina and boehmite) or functional materials in the solvent, shorten the dispersion time, and improve the stability of the slurry.
[0041] Preferably, in the above S2, the preparation method of the diaphragm slurry is specifically as follows: adding the dispersant to the water and stirring at a speed of R1, then adding the functional component and stirring at a speed of R2, frosting, adding the modified black phosphorus composite material and stirring at a speed of R3, adding the thickener and stirring at a speed of R4, adding the binder and stirring at a speed of R5 to obtain the diaphragm slurry.
[0042] More preferably, R1 is 200-2000 r / min, R2 is 2000-7000 r / min, R3 is 200-2000 r / min, R4 is 200-2000 r / min, and R5 is 200-2000 r / min.
[0043] A rotation speed within a certain range helps to fully mix the additives and materials. A low rotation speed will lead to poor slurry uniformity, and a high rotation speed may cause a large amount of air to enter the slurry, resulting in bubbles.
[0044] Preferably, in S3, the base film is selected from one or more of polyethylene film, polypropylene film, PP / PE / PP composite film, non-woven fabric, and polyimide film.
[0045] Preferably, in the above-mentioned S3, the thickness of the base film is 5 to 25 μm.
[0046] The purpose of selecting the type of base film and controlling the thickness of the base film is to make it suitable for the mainstream product market. Currently, the base film is mainly PE, and the thickness of the base film is mainly concentrated in the range of 5 to 25μm.
[0047] Preferably, in the above-mentioned S3, a coating is formed on the surface of the base film after drying, and the thickness of the coating is 0.5 to 10 μm.
[0048] A coating thickness within a certain range helps improve the separator's heat resistance and ensure the content of functional components. A coating that is too low may make coating difficult, and too few functional components may not achieve the desired effect. A coating that is too thick may cause powder shedding and excessive air permeability, affecting battery performance.
[0049] Preferably, in S3, the coating method is selected from one or more of micro-gravure coating, dip coating, and slit coating.
[0050] Preferably, in S3, the diaphragm slurry is coated on the surface of one side or both sides of the base film.
[0051] The present invention also provides a diaphragm prepared by the above preparation method.
[0052] The present invention also proposes an application of the diaphragm prepared by the above preparation method in a lithium ion battery. The above diaphragm is assembled with a positive electrode, a negative electrode and an electrolyte to form a lithium ion battery.
[0053] Preferably, the positive electrode material of the positive electrode is selected from lithium iron phosphate, lithium iron manganese phosphate, lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, LiMn x Co 1-x O2(0<x<1), LiNi x Co 1-x O2(0<x<1), LiMn x Ni 1-x O2(0<x<1), LiNi x Co y Mn 1-x- y One or more of O2 (0<x, y<1, 0<x+y<1).
[0054] Preferably, the negative electrode material of the negative electrode is selected from one or more of graphite and SiC.
[0055] Preferably, the electrolyte is selected from one or more of LiPF6, LiBF4, LiAsF6, and LiSbF6.
[0056] The beneficial effects of the present invention are:
[0057] The diaphragm obtained by the preparation method of the present invention can effectively conduct lithium and improve the wettability of the electrolyte to the diaphragm. In the present invention, black phosphorus has a high lithium ion diffusion constant, and the two-dimensional sheet can have a larger specific surface area, and the characteristic of the presence of lone pairs of electrons on its surface. On the one hand, hydroxylation can effectively curb the easy oxidation of black phosphorus due to the presence of lone pairs of electrons. At the same time, the hydroxyl group and EDOT can effectively form hydrogen bonds, which is conducive to the further in situ polymerization of EDOT on the black phosphorus surface to form PEDOT. After adding the modified black phosphorus composite material PEDOT-BP to the diaphragm coating, the lithium ion conductivity of the diaphragm is effectively improved, while the electrolyte wettability is improved, thereby improving battery performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] Figure 1 This is an SEM image of the black phosphorus nanosheet powder prepared in Example 1 of the present invention.
[0059] Figure 2 Schematic diagram of the preparation process of modified black phosphorus composite materials. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is described in detail through specific embodiments.
[0061] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.
[0062] Example 1
[0063] A method for preparing a diaphragm comprises the following steps:
[0064] S1. Red phosphorus, tin iodide, and tin powder were mixed uniformly in a mass ratio of 20:3:1 and then vacuum sealed. The mixture was heated to 650°C at 200°C / h in a tube furnace and kept warm for 1h. The mixture was cooled to 500°C for 2h after 4h and kept warm for 2h. The mixture was cooled to 200°C after 10h and finally cooled to room temperature after 5h. The mixture was washed with acetone and dried to obtain a mixture. 20g of the mixture and 1000g of N-methylpyrrolidone were ultrasonically stirred: the stirring operation was carried out at 10000r / min for 10h, and the mixture was centrifuged and vacuum dried at 60°C to obtain black phosphorus nanosheet powder.
[0065] Black phosphorus nanosheet powder and D-(+)-glucose were added to 600 mL of DMF in a mass ratio of 1:2, transferred to a Teflon stainless steel autoclave and reacted at 180°C for 3 hours, and washed and dried with ethanol to obtain hydroxylated black phosphorus; the hydroxylated black phosphorus was dispersed in ethanol at a mass ratio of 1:600, and EDOT with a mass ratio of 2 times that of the hydroxylated black phosphorus was added and continued to disperse for 15 minutes, and then a 0.055 mmol / mL FeCl3 ethanol solution with a mass ratio of 40 times that of the hydroxylated black phosphorus was added, and stirred at 6000 rpm / min for 5 minutes, then at 1500 rpm / min for 1 hour, and the product was washed and dried with ethanol to obtain a modified black phosphorus composite material PEDOT-BP;
[0066] S2. Add sodium polyacrylate to water and stir at a speed of 1500 r / min for 30 minutes, then add boehmite (particle size 1.5 μm) and stir at a speed of 5000 r / min for 60 minutes, sand in a sander for 50 minutes, add PEDOT-BP and stir at a speed of 100 r / min for 20 minutes, add sodium carboxymethyl cellulose and stir at a speed of 1000 r / min for 20 minutes, add water-based polyacrylate and stir at a speed of 1200 r / min for 20 minutes to obtain a diaphragm slurry; wherein the mass ratio of sodium polyacrylate, water, PEDOT-BP, sodium carboxymethyl cellulose, water-based polyacrylate and boehmite is 1.0:100:3:0.5:2:20;
[0067] S3. Use a micro-gravure coating process to evenly coat the diaphragm slurry on the surface of one side of the polyethylene film, dry it naturally, and form a coating on the surface of the polyethylene film to obtain a diaphragm; wherein the thickness of the polyethylene film is 12 μm; the thickness of the coating is 2 μm.
[0068] Example 2
[0069] The only difference between Example 2 and Example 1 is that the mass ratio of sodium polyacrylate, water, PEDOT-BP, sodium carboxymethyl cellulose, aqueous polyacrylate, and boehmite is 1.0:100:5:0.5:2:20.
[0070] Example 3
[0071] The only difference between Example 3 and Example 1 is that the functional component boehmite in Example 1 is replaced by alumina.
[0072] Example 4
[0073] The only difference between Example 4 and Example 1 is that the functional component boehmite in Example 1 is replaced by alumina, and the mass ratio of sodium polyacrylate, water, PEDOT-BP, sodium carboxymethyl cellulose, aqueous polyacrylate, and alumina is 1.0:100:5:0.5:2:20.
[0074] Example 5
[0075] The only difference between Example 5 and Example 1 is that the binder water-based polyacrylate in Example 1 is replaced by polyvinylidene fluoride.
[0076] Example 6
[0077] The only difference between Example 6 and Example 1 is that the binder water-based polyacrylate in Example 1 is replaced by polyvinylidene fluoride; the mass ratio of sodium polyacrylate, water, PEDOT-BP, sodium carboxymethyl cellulose, polyvinylidene fluoride, and boehmite is 1.0:100:5:0.5:2:20.
[0078] Comparative Example 1
[0079] A method for preparing a diaphragm comprises the following steps:
[0080] S1. Add sodium polyacrylate to water and stir at a speed of 1500 r / min for 30 minutes, then add boehmite (particle size 1.5 μm) and stir at a speed of 5000 r / min for 60 minutes, sand in a sander for 50 minutes, add sodium carboxymethyl cellulose and stir at a speed of 1000 r / min for 20 minutes, add water-based polyacrylate and stir at a speed of 1200 r / min for 20 minutes to obtain a slurry for a lithium battery separator; wherein the mass ratio of sodium polyacrylate, water, sodium carboxymethyl cellulose, water-based polyacrylate and boehmite is 1.0:100:0.5:2:20;
[0081] S2. Use a micro-gravure coating process to evenly coat the lithium battery separator slurry on the surface of one side of the polyethylene film, dry it naturally, and form a coating on the surface of the polyethylene film to obtain a separator; wherein the thickness of the polyethylene film is 12 μm; the thickness of the coating is 2 μm.
[0082] Comparative Example 2
[0083] A method for preparing a diaphragm comprises the following steps:
[0084] S1. Add sodium polyacrylate to water and stir at a speed of 1500 r / min for 30 min, then add boehmite (particle size 1.5 μm) and stir at a speed of 5000 r / min for 60 min, sand in a sander for 50 min, add sodium carboxymethyl cellulose and stir at a speed of 1000 r / min for 20 min, add polyvinylidene fluoride and stir at a speed of 1200 r / min for 20 min to obtain a slurry for a lithium battery separator; wherein the mass ratio of sodium polyacrylate, water, sodium carboxymethyl cellulose, polyvinylidene fluoride and boehmite is 1.0:100:0.5:2:20;
[0085] S2. Use a micro-gravure coating process to evenly coat the lithium battery separator slurry on the surface of one side of the polyethylene film, dry it naturally, and form a coating on the surface of the polyethylene film to obtain a separator; wherein the thickness of the polyethylene film is 12 μm; the thickness of the coating is 2 μm.
[0086] Comparative Example 3
[0087] A method for preparing a diaphragm comprises the following steps:
[0088] S1. Add sodium polyacrylate to water and stir at a speed of 1500 r / min for 30 minutes, then add aluminum oxide (particle size 1.5 μm) and stir at a speed of 5000 r / min for 60 minutes, sand in a sander for 50 minutes, add sodium carboxymethyl cellulose and stir at a speed of 1000 r / min for 20 minutes, add water-based polyacrylate and stir at a speed of 1200 r / min for 20 minutes to obtain a slurry for a lithium battery separator; wherein the mass ratio of sodium polyacrylate, water, sodium carboxymethyl cellulose, water-based polyacrylate and aluminum oxide is 1.0:100:0.5:2:20;
[0089] S2. Use a micro-gravure coating process to evenly coat the lithium battery separator slurry on the surface of one side of the polyethylene film, dry it naturally, and form a coating on the surface of the polyethylene film to obtain a separator; wherein the thickness of the polyethylene film is 12 μm; the thickness of the coating is 2 μm.
[0090] Comparative Example 4
[0091] A method for preparing a diaphragm comprises the following steps:
[0092] S1. Add sodium polyacrylate to water and stir at a speed of 1500 r / min for 30 min, then add alumina (particle size 1.5 μm) and stir at a speed of 5000 r / min for 60 min, sand in a sander for 50 min, add sodium carboxymethyl cellulose and stir at a speed of 1000 r / min for 20 min, add polyvinylidene fluoride and stir at a speed of 1200 r / min for 20 min to obtain a slurry for a lithium battery separator; wherein the mass ratio of sodium polyacrylate, water, sodium carboxymethyl cellulose, polyvinylidene fluoride and alumina is 1.0:100:0.5:2:20;
[0093] S2. Use a micro-gravure coating process to evenly coat the lithium battery separator slurry on the surface of one side of the polyethylene film, dry it naturally, and form a coating on the surface of the polyethylene film to obtain a separator; wherein the thickness of the polyethylene film is 12 μm; the thickness of the coating is 2 μm.
[0094] The separators prepared in Examples 1-6 and Comparative Examples 1-4 were cut into 67 mm wide separators and wound to form batteries, yielding soft-pack batteries. The positive electrode material was lithium manganese iron phosphate, the negative electrode material was graphite, and the electrolyte was LiPF6. The separators prepared in Examples 1-6 and Comparative Examples 1-4 were tested for thickness, wettability, and ionic conductivity. Batteries assembled with the separators prepared in Examples 1-6 and Comparative Examples 1-4 were tested for capacity retention after 200 cycles. The test results are shown in Table 1.
[0095] Table 1
[0096] Battery Type Thickness (μm) Ionic conductivity (ms / cm) <![CDATA[Wetting rate (mm 2 / S)]]> Capacity retention rate after 200 cycles (%) Example 1 14.08 1.65 15.6 91.4 Example 2 13.87 1.75 14.2 92.1 Example 3 14.22 1.57 14.7 89.7 Example 4 14.10 1.59 15.8 94.3 Example 5 13.97 1.65 14.3 94.1 Example 6 13.99 1.73 14.9 93.6 Comparative Example 1 13.95 0.74 4.7 83.2 Comparative Example 2 14.23 0.81 3.9 87.4 Comparative Example 3 14.19 0.80 5.5 85.9 Comparative Example 4 13.91 0.82 4.8 89.1
[0097] From the data in Table 1, it can be seen that the thickness of Examples 1 to 6 is similar to that of Comparative Examples 1 to 4. Due to the addition of the modified black phosphorus composite material PEDOT-BP, the ionic conductivity of the Example diaphragm is significantly higher than that of the Comparative Example diaphragm. At the same time, the infiltration rate of the electrolyte into the diaphragm was tested, and it can be seen that the infiltration rate of the Example is about three times that of the Comparative Example. After 200 cycles of capacity retention test on the batteries assembled using the Example and Comparative Example diaphragms, the average capacity retention rate of the six Example batteries was 92.53%, and the average capacity retention rate of the four Comparative Example batteries was 86.40%. It can be seen that the cycle performance of the battery assembled with the diaphragm with the modified black phosphorus composite material PEDOT-BP has been significantly improved.
[0098] In summary, the separator provided by the present invention has excellent ionic conductivity and electrolyte wettability, and helps to improve the battery cycle performance.
[0099] The above description is only a preferred specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any technician familiar with the technical field, within the technical scope disclosed by the present invention, who makes equivalent replacements or changes based on the technical solution and inventive concept of the present invention, should be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a diaphragm, characterized in that: The following steps are involved: S1, modifying black phosphorus to obtain a modified black phosphorus composite material; S2. Mixing the modified black phosphorus composite material, dispersant, water, functional component, thickener, and binder to obtain a diaphragm slurry; S3. Apply the diaphragm slurry on the surface of the base film and let it dry.
2. The preparation method according to claim 1, characterized in that In the above-mentioned S1, the modification treatment includes: uniformly mixing black phosphorus, D-(+)-glucose, and a solvent, heating the reaction in a reactor for reaction, washing and drying to obtain hydroxylated black phosphorus; dispersing the hydroxylated black phosphorus in a solvent, then adding EDOT and FeCl3 solution, uniformly dispersing, washing, and drying to obtain the product.
3. The preparation method according to claim 2, characterized in that The mass ratio of black phosphorus, D-(+)-glucose and solvent is (1-3): (1-3): (500-900); the mass ratio of hydroxylated black phosphorus, EDOT and FeCl3 solution is (1-3): (1-7): (20-100); the solvent is selected from one or more of N-methylpyrrolidone, acetone, N,N-dimethylformamide and ethanol; the heating temperature is 100-200°C; and the FeCl3 solution is an ethanol solution of FeCl3.
4. The preparation method according to claim 1, characterized in that In the above S1, the preparation method of black phosphorus comprises the following steps: uniformly mixing red phosphorus, tin iodide and tin powder, and calcining to obtain a mixture; stirring the mixture and a dispersant, centrifuging and drying to obtain black phosphorus.
5. The preparation method according to claim 4, characterized in that The mass ratio of the red phosphorus, tin iodide and tin powder is (10-30): (2-7): (0.5-2); the calcination treatment includes first heating to 600-700°C at a rate of 150-200°C / h and keeping the temperature for 1-2h; then cooling to 450-500°C within 4-5h and keeping the temperature for 1-2h; then cooling to 200-250°C within 9-10h; and finally cooling to room temperature within 5-6h; the mass ratio of the mixture to the dispersant is (10-50): (300:600); the dispersant is N-methylpyrrolidone.
6. The preparation method according to claim 1, characterized in that In the S2, the mass ratio of the dispersant, water, modified black phosphorus composite material, thickener, binder, and functional component is (0.1-10):100:(0.1-10):(0.5-15):(0.1-10):(10-80).
7. The preparation method according to claim 1, characterized in that In the S2, the functional component is selected from one or more of ceramic solid particles and PVDF particles; the thickener is selected from one or more of sodium carboxymethyl cellulose, carboxymethyl hydroxypropyl cellulose, methyl hydroxyethyl cellulose, and hydroxyethyl cellulose; the binder is selected from one or more of water-based polyacrylate, polyurethane acrylate, polyether acrylate, polyurethane, epoxy resin, and polyvinylidene fluoride; and the dispersant is selected from one or more of sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, and sodium polycarboxylate.
8. The preparation method according to claim 1, characterized in that In the above-mentioned S3, the base film is selected from one or more of polyethylene film, polypropylene film, PP / PE / PP composite film, non-woven fabric, and polyimide film; the thickness of the base film is 5 to 25 μm; after drying, a coating is formed on the surface of the base film, and the thickness of the coating is 0.5 to 10 μm.
9. A diaphragm, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of a diaphragm obtained by the preparation method according to any one of claims 1 to 8 in a lithium ion battery.